2021
DOI: 10.3389/fmicb.2021.733631
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Novel Viruses Associated With the Invasive Cane Toad (Rhinella marina) in Its Native and Introduced Ranges

Abstract: Cane toads (Rhinella marina) are notoriously successful invaders: from 101 individuals brought to Australia in 1935, poisonous toads now cover an area >1.2 million km2 with adverse effects on native fauna. Despite extensive research on the role of macroparasites in cane toad invasion, viral research is lagging. We compared viral prevalence and diversity between toads in their native range (French Guiana, n=25) and two introduced ranges: Australia (n=151) and Hawai’i (n=10) with a metatranscriptomic and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 77 publications
0
9
0
Order By: Relevance
“…Largemouth bass virus and mandarin fish ranavirus are highly lethal in farmed populations, causing 95-100% mortality [60, 61]. Our metatranscriptomic analysis also identified a novel iridovirus in E. tutuilae that fell sister to erythrocytic necrosis virus (ENV) [51] and clustered with other erythrocytic-like viruses identified in amphibians and reptiles [52, 53, 54, 55]. ENV was the closest relative across all proteins identified (Supplementary Table 2).…”
Section: Resultsmentioning
confidence: 96%
“…Largemouth bass virus and mandarin fish ranavirus are highly lethal in farmed populations, causing 95-100% mortality [60, 61]. Our metatranscriptomic analysis also identified a novel iridovirus in E. tutuilae that fell sister to erythrocytic necrosis virus (ENV) [51] and clustered with other erythrocytic-like viruses identified in amphibians and reptiles [52, 53, 54, 55]. ENV was the closest relative across all proteins identified (Supplementary Table 2).…”
Section: Resultsmentioning
confidence: 96%
“…Members of the family Picornaviridae are small, nonenveloped, positive single-stranded RNA viruses that can cause a variety of human diseases such as poliomyelitis, common cold, myocarditis, and hepatitis [ 46 ]. Many PicoVs infecting amphibians have been discovered by sequencing over the years [ 19 , 47 , 48 , 49 , 50 ]. The identification of AtPicoVs will help to expand our knowledge of the family Picornaviridae , which will facilitate the study of amphibian PicoVs in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The identification of AtPicoVs will help to expand our knowledge of the family Picornaviridae , which will facilitate the study of amphibian PicoVs in the future. On the other hand, thousands of novel viral genomes from invertebrate samples have recently identified by meta-transcriptomic studies [ 47 , 51 , 52 ]. In our study, we identified several invertebrate RNA viruses from three libraries (SC-liver, SC-lung, and SC-gut) derived from liver, lung, and gut samples.…”
Section: Discussionmentioning
confidence: 99%
“…The discovery of DNA viruses primarily relies on either tissue DNA sequencing or PCR-based approaches. Many new viruses have been discovered this way [ 27 29 ], however a novel approach is to utilise transcriptomic data to discover DNA viruses through bioinformatic approaches [ 15 , 30 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…We identified a novel member of the DNA subfamily of the Papillomaviridae family, namely Secondpapillomavirinae , which to-date only contains one formally recognised virus [ 45 ]. The Secondpapillomavirinae viruses comprise greatly condensed viral genomes, conserving only the core E1-E2-L2-L1 genes, which may represent ancestral sequences that diversified in lower vertebrates [ 30 , 33 , 46 ]. Oreolalax rhodostigmatus papillomavirus is the second amphibian papillomavirus discovered, and the newest member of the Secondpapillomavirinae subfamily of fish and amphibian papillomaviruses (Fig.…”
Section: Discussionmentioning
confidence: 99%